2019
DOI: 10.3390/app9183672
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-Performance Evaluation of Bicycle Helmets for Convective and Evaporative Heat Loss at Low and Moderate Cycling Speeds

Abstract: The main objective of the study was to investigate the thermal performance of five (open and closed) bicycle helmets for convective and evaporative heat transfer using a nine-zone thermal manikin. The shape of the thermal manikin was obtained by averaging the 3D-point coordinates of the head over a sample of 85 head scans of human subjects, obtained through magnetic resonance imaging (MRI) and 3D-printed. Experiments were carried out in two stages, (i) a convective test and (ii) an evaporative test, with ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…All the values in matrix TR bR thus become TR bR. The heat dissipation on the belt surfaces can be easily calculated [31], thereby yielding function k(TR bR ,…). The thermal balance of the belt can be expressed as…”
Section: Thermal Analysis Of the Beltmentioning
confidence: 99%
See 2 more Smart Citations
“…All the values in matrix TR bR thus become TR bR. The heat dissipation on the belt surfaces can be easily calculated [31], thereby yielding function k(TR bR ,…). The thermal balance of the belt can be expressed as…”
Section: Thermal Analysis Of the Beltmentioning
confidence: 99%
“…Hence, the density of air is computed by using the incompressible ideal gas equation and its change is negligible. The finite volume method used in this analysis solves the governing equations in integral form, as shown below [31]: j j ∂ Figure 9. Polyhedral mesh for the numerical analysis.…”
Section: Modeling the Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Contributions can focus on sensors, wearable hardware, algorithms, or integrated monitoring systems. We organized the different papers according to their contributions to the main parts of the monitoring and control engineering scheme applied to human health applications, namely papers focusing on measuring/sensing of physiological variables [24][25][26][27][28][29][30][31], contributions describing research on the modelling of biological signals [32][33][34][35][36][37][38], papers highlighting health monitoring applications [39][40][41][42], and finally examples of control applications for human health [43][44][45][46][47][48]. In comparison to biomedical engineering, we envision that the field of human health engineering also covers applications on healthy humans (e.g., sports, sleep, and stress) and thus not only contributes to develop technology for curing patients or supporting chronically ill people, but also for disease prevention and optimizing human well-being more generally.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%
“…Since their method is based on cheap PPG sensing elements that can be integrated in wearables, this approach can significantly contribute to (preventive) health monitoring as, compared to classical (expensive) cuff-based methods, as it allows 24/7 measurements. The work of Mukunthan et al [27] describes the use of a nine-zone thermal manikin head for measuring convective and evaporative heat losses from a human head wearing a bicycle helmet. They demonstrated that the design of the helmet, mainly characterized by the number and position of vent openings and the presence of internal air channels, has a significant effect on the heat losses of a human head when covered by a bicycle helmet.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%